2022
DOI: 10.2196/37856
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Studying Awareness of a Digital Health Campaign on Facebook: Pilot Study Comparing Young Adult Subsamples

Abstract: Background Mass media campaigns for preventive health messaging have been shown to be effective through years of research. However, few studies have assessed the effectiveness of campaigns on digital media, which is currently how youths and young adults are primarily consuming media. In particular, a platform that can accurately assess exposure to digital messaging in a real-life setting has yet to be developed. Objective This study examines the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Cell sizes between the study conditions were reduced at the second FU, which may have reduced the statistical power to below the levels needed to detect some dose-response outcomes of interest. Previous studies have shown the dose-response effects of anti-industry messaging on vaping-related content exposure and attitudinal outcomes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell sizes between the study conditions were reduced at the second FU, which may have reduced the statistical power to below the levels needed to detect some dose-response outcomes of interest. Previous studies have shown the dose-response effects of anti-industry messaging on vaping-related content exposure and attitudinal outcomes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a great need for more research on the relationship between digital media and health behaviors, social norms, and social networks. Although research is being conducted to determine what digital media as an intervention tool would look like, how it works, and how effective it is [ 13 , 14 ], these studies have only scratched the surface [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a great need for more research on the relationship between digital media and health behaviors, social norms, and social networks. While research is being conducted to determine what digital media as an intervention tool would look like, how it works, and how effective it is [13][14], these studies have only scratched the surface [15].…”
Section: Original Manuscriptmentioning
confidence: 99%
“…One important objective of future research using social media platforms is to determine how to optimize study designs and responses to recruitment and intervention methods. 29 …”
Section: Introductionmentioning
confidence: 99%